Giri Kawangi Pujaran Giri Harja 2 sebagai Pelestari Wayang Golek di Kecamatan Ujungberung 1995-2025 - Teddiansyah Nata Negara (UIN Sunan Gunung Djati Bandung, 2025)
Padepokan Giri Harja is a prominent center for the preservation and development of Wayang Golek, a traditional Sundanese puppet art, in West Java. Founded by the legendary puppeteer Abeng Sunarya, the institution has evolved into an artistic hub that fosters cultural education across generations. This study explores the significant role of Pujaran Giri Harja 2, led by puppeteer Awan Kartanda Suanda Ade Kosasih, a non-lineal disciple who has been officially acknowledged within the Sunarya lineage of cultural transmission. Using historical and oral history methodologies, the research investigates informal learning processes, spiritual and cultural values, and the dynamics of succession within the Giri Harja community. Findings reveal that Giri Harja does not limit its teachings to biological heirs but extends its legacy to dedicated disciples who embody the spiritual and cultural ethos of Sundanese puppetry. The pedagogy employed is experiential and rooted in daily practice, strengthening intergenerational bonds through emotional closeness and lived experience. Symbolic mechanisms, such as verbal certification (non-formal “diplomas”), serve as markers of skill recognition. The success of Giri Harja in extending its influence nationally and internationally is further supported by an inclusive and adaptive succession strategy. This study affirms that Pujaran Giri Harja 2 stands as a tangible representation of an open and spiritually rooted cultural inheritance system resilient to temporal changes.